Depresión como factor asociado a vértigo posicional paroxístico benigno en pacientes del Hospital Víctor Lazarte Echegaray - Cano Luján, Eduardo Ricardo (2022)
This project encompasses a study to determine if depression is an associated factor for benign paroxysmal positional vertigo in patients at the Víctor Lazarte Echegaray Hospital; through an analytical, observational, retrospective study of cases and controls; The population will be made up of patients treated by the Outpatient Otorhinolaryngology Clinics of the Víctor Lazarte Echegaray Hospital during the 2016-2019 period and who meet the following selection criteria; Since the study corresponded to a case-control design, the Odss Ratio (OR) will be obtained for depression in terms of its association with the appearance of benign paroxysmal positional vertigo. The 95% confidence interval of the corresponding statistician was calculated.